Health workforce malldistribution: Lesson from central Lampung Regency in Indonesia - Simon Sumanjoyo Hutagalung; Dedy Hermawan; Devi Aulia (Intelektual Pustaka Media Utama, 2020)
The purpose of this study is to explain: (1) Distribution of health workers in basic health services in Central Lampung, and (2). Factors that influence the process of procurement and distribution of health workers in primary health care in Central Lampung. Research conducted with this descriptive qualitative method involved health stakeholders in 34 health centers and 17 hospitals in the region. The results of this study include: (a). Analysis of the Distribution of Health Workers by Region, it is known that the pattern of distribution is not balanced and there are some districts that do not have several types of health workers. (b). Analysis of power distribution based on health workplaces is known that the majority of health workers are in health centers, even midwives and nurses are mostly in health centers and some types of health workers are not yet available in health centers. Also known factors that influence the process of procurement and distribution of health workers in primary health care include structural and environmental factors.